29.5k views
3 votes
Solve for x: 5 [(x/6)-2] = 2x + 4

User Tysonjh
by
4.5k points

2 Answers

2 votes

Answer:

x = -12

Step-by-step explanation

User Anhlc
by
5.3k points
6 votes

Answer:

-12 =x

Explanation:

5 [(x/6)-2] = 2x + 4

Distribute

5/6x - 10 = 2x+4

Subtract 5/6x from each side

5/6x -10 -5/6x = 2x -5/6x +4

-10 =2x -5/6x +4

Subtract 4 from each side

-10-4 = 2x - 5/6x

Get a common denominator for the right side

-14 = 12/6x - 5/6x

-14 = 7/6x

Multiply each side by 6/7

-14 * 6/7 = 7/6 x * 6/7

-12 =x

User Urvishsinh Mahida
by
5.4k points